2018
DOI: 10.1007/s10902-018-9996-9
|View full text |Cite
|
Sign up to set email alerts
|

Linking Managerial Coaching and Leader–Member Exchange on Work Engagement and Performance

Abstract: This study investigates how individual-and unit-level performance can be fostered by supervisors' behavioural styles (managerial coaching) and the personal relationship between supervisor and subordinate (leader-member exchange, LMX). The JD-R model holds that good leadership serves as a job resource and triggers a motivational process that will lead through work engagement to good performance. This study first introduces and validates novel measurement instruments for managerial coaching, LMX, and self-rated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(118 citation statements)
references
References 83 publications
(135 reference statements)
9
108
0
1
Order By: Relevance
“…Thus, the present study represents a step forward with respect to previous research in analyzing and confirming the effect of leaders developing a coaching-based leadership style on their levels of PsyCap after participating in a training intervention. Moreover, our findings for the impact of the intervention on work engagement are in line with previous research that found a positive link between this variable and the leader's coaching (Lin et al, 2016;Taplin, 2017, 2018;Ali et al, 2018;Lee et al, 2018;Tanskanen et al, 2019). Despite the increasing number of studies exploring this link, work engagement has mostly been evaluated in non-experimental cross-sectional studies and as an employee-related outcome.…”
Section: Post-intervention Effectssupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, the present study represents a step forward with respect to previous research in analyzing and confirming the effect of leaders developing a coaching-based leadership style on their levels of PsyCap after participating in a training intervention. Moreover, our findings for the impact of the intervention on work engagement are in line with previous research that found a positive link between this variable and the leader's coaching (Lin et al, 2016;Taplin, 2017, 2018;Ali et al, 2018;Lee et al, 2018;Tanskanen et al, 2019). Despite the increasing number of studies exploring this link, work engagement has mostly been evaluated in non-experimental cross-sectional studies and as an employee-related outcome.…”
Section: Post-intervention Effectssupporting
confidence: 90%
“…Specifically, leader-as-coach training programs aim to enhance leadership quality in organizations by providing training in coaching skills (Graham et al, 1994;Hagen, 2012;Grant and Hartley, 2014). The increased demand for leaders with coaching skills is generally attributed to the many recognized benefits, such as enhanced employee and organizational performance (Liu and Batt, 2010;Ellinger et al, 2011;Kim et al, 2013;Tanskanen et al, 2019). Additionally, previous studies have identified leaders as coaches as a powerful developmental intervention for motivating, developing, and retaining employees in organizations (Ellinger et al, 2011).…”
Section: Coaching-based Leadership Intervention and Its Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…As a kind of management approach to help subordinates improve existing competence, inspire possible intelligence, and maximise personal potential (Wagstaff, Arthur, & Hardy, 2018), managerial coaching has drawn growing interest both theoretically and in practice (Matsuo, 2018;Tanskanen, Mäkelä, & Viitala, 2018;Wagstaff et al, 2018). Compared with a traditional leadership's exertion of administration, command, and control, the approach of managerial coaching relies on guidance, facilitation, and inspiration (Tanskanen et al, 2018). The central purpose of managerial coaching is to prompt subordinates' self-efficacy, performance, and development (Woo, 2017), specifically through setting and communicating clear expectations, broadening subordinates' perspectives, and giving feedback (Ellinger et al, 2011).…”
Section: Managerial Coachingmentioning
confidence: 99%
“…Kyselyssä käsiteltiin laajasti henkilöstöjohtamiseen liittyviä teemoja ja käytänteitä. Vuorovaikutusta esimiehen kanssa selvitettiin Leader-Member Exchange (LMX) -teoriaan pohjautuvilla 12 kysymyksellä (Danserau, Graen & Haga, 1975;Graen & Uhl-Bien, 1995), jotka on vahvistettu LMX-UVA -kysymyksiksi (Tanskanen, Mäkelä & Viitala, 2018) (Liite 1). Väittämiä olivat esimerkiksi "Kykenemme aidosti kuuntelemaan toistemme mielipiteitä" ja "Meidän on helppo ottaa puheeksi erilaiset työhön liittyvät asiat".…”
Section: Tutkimuksen Toteuttaminenunclassified